Pengaruh Kreativitas Belajar Dan Kemampuan Komunikasi Mahasiswa Terhadap Hasil Belajar Mata Kuliah Ekonomi Makro Pada Mahasiswa Pendidikan Akuntansi Fakultas Keguruan Dan Ilmu Penndidikan UniversitasMuhammadiyah Surakarta Tahun 2015 - Murdiastuti, Lili, Drs. Djoko Suwandi, M.Pd (2016)
The purpose of this research are: 1) To determine the influence of creativity in learning on learning outcomes. 2) To determine the effect of communication skills of students on learning outcomes. 3) To determine the influence of creativity in learning and communication skills of students on learning outcomes. This research is descriptive quantitative research with a conclusion through statistical methods. The population in this study were all students of the Faculty of Teacher Training and Education Program of Accounting Education Studies University of Muhammadiyah Surakarta 2015/2016 Forces. samples are taken as 146 students by random sampling. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, F, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 15.193 + 1.014 X1 + 0.516 X2. The equation shows that the learning outcomes are influenced by the creativity of students learning and communication skills. The conclusions drawn are: 1) Creativity learning to the learning outcomes are acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, 7.244> 1.960 and the significance value <0.05, namely 0.000 with the relative contribution of 81.5% and 26.2% effective contribution. 2) The ability to communicate students' learning outcomes are acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 3.169> 1.960 and the significance value <0.05, namely 0.002 with the relative contribution of 18.5% and the effective contribution of 6%. 3) Creativity learning and communication skills of students to the learning outcomes are acceptable. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 34.031> 3.000 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.322 indicates that the influence of creativity in learning and communication skills of students towards learning outcomes is 32.2%, while the rest influenced by other variables.